1998
DOI: 10.1523/jneurosci.18-22-09517.1998
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Integration in Striate Cortical Simple Cells

Abstract: Simple cells in the visual cortex respond to the precise position of oriented contours (Hubel and Wiesel, 1962). This sensitivity reflects the structure of the simple receptive field, which exhibits two sorts of antagonism between on and off inputs. First, simple receptive fields are divided into adjacent on and off subregions; second, within each subregion, stimuli of the reverse contrast evoke responses of the opposite sign: push-pull (Hubel and Wiesel, 1962;Palmer and Davis, 1981;Jones and Palmer, 1987;Fers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
263
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(291 citation statements)
references
References 87 publications
25
263
1
2
Order By: Relevance
“…This balance of currents immediately implies that the inhibitory conductance must be higher than the excitatory (g E V E Ӎ g I ͉V I ͉ f g I Ӎ (V E ͉͞V I ͉)g E ϭ 7g E ). The high (inhibitory) conductance regime at which the model operates is also supported by recent experiments: large inhibitory conductances, evoked by visual stimuli, have been observed experimentally in visual cortical cells (40,41).…”
Section: Discussionsupporting
confidence: 62%
“…This balance of currents immediately implies that the inhibitory conductance must be higher than the excitatory (g E V E Ӎ g I ͉V I ͉ f g I Ӎ (V E ͉͞V I ͉)g E ϭ 7g E ). The high (inhibitory) conductance regime at which the model operates is also supported by recent experiments: large inhibitory conductances, evoked by visual stimuli, have been observed experimentally in visual cortical cells (40,41).…”
Section: Discussionsupporting
confidence: 62%
“…It is also possible that the balance of excitation and inhibition plays an important role in regulating the tuning of spiking outputs of neurons near pinwheel centers. There is substantial evidence for shunting inhibition in V1 neurons [1,10,30,44], though the tuning of such inhibition is not entirely clear [1,44]. Shunting inhibition can effectively clamp the membrane potential, which has the effect of reducing the influence of excitatory synaptic inputs, and also reducing the variability of membrane potential [44].…”
Section: Mechanisms Regulating Spike Tuning Near Pinwheel Centersmentioning
confidence: 99%
“…Previous experiments have shown that single inhibitory cells elicit rather small changes in conductance and weak IPSPs (Ͻ1 mV in pyramidal cells depolarized by Յ20 mV; Gupta et al 2000;Thomson and Deuchars 1997). In contrast, in vivo intracellular recordings reveal much larger changes in inhibitory conductance during visual processing (Anderson et al 2000;BorgGraham et al 1998;Hirsch et al 1998). Taken together, these data indicate that inhibitory cells recruited by horizontal connections do not perform in isolation during cortical processing, but as part of coordinated inhibitory networks.…”
Section: Physiological Properties Of Emergent Inhibitionmentioning
confidence: 72%